2006
DOI: 10.1021/ja060140u
|View full text |Cite
|
Sign up to set email alerts
|

Metal Supported on Dendronized Magnetic Nanoparticles:  Highly Selective Hydroformylation Catalysts

Abstract: A method for homogenizing heterogeneous catalyst is described. The method is based on growing polyaminoamido (PAMAM) dendrons on silica-coated magnetic nanoparticles. After the dendronizing process, the silica-coated magnetic nanoparticles are more stable and more soluble in organic solvents. The dendronized particles are phosphonated, complexed with [Rh(COD)Cl]2, and applied in catalytic hydroformylation reactions. These new catalysts are proven to be highly selective and reactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
231
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(236 citation statements)
references
References 62 publications
2
231
0
3
Order By: Relevance
“…Moreover, the ability of magnetic nanoparticles to serve efficiently as nano-support for organocatalytic systems has been recently reported [22][23][24][25][26][27][28][29][30][31][32]. We have described the highly selective hydroformylation reaction using rhodium catalysts supported on dendronized magnetic nanoparticles [33]. We have also developed a catalytic system for the chemoselective hydrogenation of α, β-unsaturated aldehydes and alkynes, based on platinum nanoparticles supported on nano-magnetite, Fe 3 O 4 , modified with ionic liquid groups [34].…”
Section: Open Accessmentioning
confidence: 99%
“…Moreover, the ability of magnetic nanoparticles to serve efficiently as nano-support for organocatalytic systems has been recently reported [22][23][24][25][26][27][28][29][30][31][32]. We have described the highly selective hydroformylation reaction using rhodium catalysts supported on dendronized magnetic nanoparticles [33]. We have also developed a catalytic system for the chemoselective hydrogenation of α, β-unsaturated aldehydes and alkynes, based on platinum nanoparticles supported on nano-magnetite, Fe 3 O 4 , modified with ionic liquid groups [34].…”
Section: Open Accessmentioning
confidence: 99%
“…in situ removal of water and moisture absorbing materials are the two options [25][26][27], which were often observed with minimum success and inconsistent yields [25][26][27]. Recent mechanism studies had suggested that moisture was not the real problem and the catalysts offering more surface area have proven to be more useful [28][29][30][31]. The use of Fe 3 O 4 @SiO 2 was first of its sort and near doubling of reaction yield is in expected lines considering our similar observation with thiophenes, terpyridine, quinazoline and isoxazole [23].…”
Section: Synthesis Of 2-amino-5-carboethoxy-4-hydroxypyrimidine Withoutmentioning
confidence: 99%
“…The nanomaterial based catalysis is not reported for pyrimidine synthesis and our group has recently reported that Fe 3 O 4 @SiO 2 acts as an inert support in some organic reactions. This inert solid support catalyst was shown to give significantly improved yields for reactions involving ring cyclizations [23,28,29]. The mechanism seems to be intermediate stabilization due to its interaction with silica surface.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, novel supports that ensure both good recyclability and catalytic activity are still desirable. MNP have recently appeared as a new type of catalyst support because of their easy preparation and functionalization, large surface area ratio, facile separation via magnetic force as well as low toxicity and price (Yoon et al, 2003;Stevens et al, 2005;Lee et al, 2006;Abu-Reziq et al, 2006;Luo et al, 2008). These features have made MNP a promising alternate of porous/mesoporous catalyst supports.…”
Section: Ionic Liquids Immobilized On Mnp and Their Applications In Omentioning
confidence: 99%